2021
DOI: 10.1364/optica.412201
|View full text |Cite
|
Sign up to set email alerts
|

Optomechanical wave mixing by a single quantum dot

Abstract: Wave mixing is an archetypical phenomenon in bosonic systems. In optomechanics, the bidirectional conversion between electromagnetic waves or photons at optical frequencies and elastic waves or phonons at radio frequencies is building on precisely this fundamental principle. Surface acoustic waves (SAWs) provide a versatile interconnect on a chip and thus enable the optomechanical control of remote systems. Here we report on the coherent nonlinear three-wave mixing between the coherent fields of two radio freq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 65 publications
1
46
0
Order By: Relevance
“…Recent studies have focused on light scattering experiments from a single semiconductor QD in the presence of SAW fields. 8,9 There, it was shown that the treatment of the SAW in the semiclassical limit by simply considering a timedependent transition energy of the QD's leads to excellent agreements with the experiments. As first benchmark for our quantum acoustic model we consider the semiclassical limit of a coherent phonon state with a large amplitude.…”
Section: A Semiclassical Limitmentioning
confidence: 95%
See 3 more Smart Citations
“…Recent studies have focused on light scattering experiments from a single semiconductor QD in the presence of SAW fields. 8,9 There, it was shown that the treatment of the SAW in the semiclassical limit by simply considering a timedependent transition energy of the QD's leads to excellent agreements with the experiments. As first benchmark for our quantum acoustic model we consider the semiclassical limit of a coherent phonon state with a large amplitude.…”
Section: A Semiclassical Limitmentioning
confidence: 95%
“…Our approach to approximate this situation is to expand the equations in powers of the light field to retrieve the optical signal in the second order of E which is sufficient to simulate the optical scattering spectrum. 8 Therefore, we express the generating functions into a series Y = Y (0) +Y (1) +Y (2) +. .…”
Section: Expansion For Weak Optical Drivingmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Conversely, optical or electrical control of single quantum states confined to a QD is challenging, nonetheless intensely pursued in fundamental research. [17][18][19][20] Over the last decade, a major progress has been achieved in measuring [21][22][23] and controlling [24][25][26] the coherence of optical transitions attributed to the bound electron-hole pair, forming a QD exciton. This was achieved by performing coherent ultrafast nonlinear spectroscopy, 27 in particular four-wave mixing (FWM) on photonic devices hosting InGaAs QDs.…”
Section: Introductionmentioning
confidence: 99%